Pengaruh Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Pada Siswa Kelas XII IPS SMA Negeri 6 Gowa - Gita Damansi Putri; Masnawaty Sangkala; Nuraisyiah (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of entrepreneurial knowledge on entrepreneurial interest in class XII students of the IPS program of SMA Negeri 6 Gowa. The variables in this study are entrepreneurial knowledge as the independent variable and entrepreneurial interest as the dependent variable. The population of this study were all students of class XII IPS 1 and XII IPS 2 of SMA Negeri 6 Gowa. The sampling technique used the Total Sampling Technique, samples from the population were obtained from the entire population with a sample of 39 students. The data collection techniques used were observation and questionnaires. The data analysis technique used is descriptive percentage analysis, instrument testing and hypothesis testing. Based on the results of the data analysis that has been carried out, the results of the descriptive analysis of entrepreneurial knowledge were obtained at 81.77 percent which was very high and the interest in entrepreneurship was 68.85 percent which was classified as high. From the results of the simple linear regression analysis, entrepreneurial knowledge was obtained Y = 8.110 + 0.823X, which means that for every 1 additional value of entrepreneurial knowledge, the value of entrepreneurial interest increases by . While the product moment correlation test obtained a value of 681 correlation coefficients and was in the very low category, which means that the influence of entrepreneurial knowledge on entrepreneurial interest is very strong. The results of the determination coefficient analysis (r2) obtained a value (r2) = 0.463 which means that entrepreneurial knowledge has a contribution to entrepreneurial interest of 5 percent and the remaining 95 percent is influenced by other factors. Meanwhile, from the results of the t-test analysis, a significant value of 0.001 <0.05 was obtained, which means.